2018
DOI: 10.1016/j.fct.2018.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral toxicity of sodium cyanide following oral ingestion in rats: Dose-dependent onset, severity, survival, and recovery

Abstract: Sodium cyanide (NaCN) is a commonly and widely used industrial and laboratory chemical reagent that is highly toxic. Its availability and rapid harmful/lethal effects combine to make cyanide a potential foodborne/waterborne intentional-poisoning hazard. Thus, laboratory studies are needed to understand the dose-dependent progression of toxicity/lethality following ingestion of cyanide-poisoned foods/liquids. We developed an oral-dosing method in which a standard pipette was used to dispense a sodium cyanide so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…DMTS did not appear to have a significant impact on the rate or degree of behavioural recovery, but instead only promoted survival. Our past research has shown that untreated survivors typically recover within a 5‐hour behavioural assessment and perform equivalently to baseline levels the following day . The recovery observed here in survivors that received lower DMTS doses is equivalent to our past work and suggests that any persistent behavioural deficits in the current study were most likely resulting from the high‐dose DMTS injection.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…DMTS did not appear to have a significant impact on the rate or degree of behavioural recovery, but instead only promoted survival. Our past research has shown that untreated survivors typically recover within a 5‐hour behavioural assessment and perform equivalently to baseline levels the following day . The recovery observed here in survivors that received lower DMTS doses is equivalent to our past work and suggests that any persistent behavioural deficits in the current study were most likely resulting from the high‐dose DMTS injection.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, a test that begins immediately after cyanide poisoning and that continues for several hours would be ideal for capturing the time course of cyanide‐induced deficits, including onset and recovery. In this regard, a recent study by some of the present authors characterized NaCN ingested acutely (4‐64 mg/kg) and revealed a rapid and dose‐dependent decrease across multiple response measures in a 5‐hour operant task (variable‐interval 90‐second schedule of food pellet reinforcement after lever pressing). In that study, deaths occurred within the first hour and no fatalities were ever observed thereafter.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations